Economic Potentials and Use Dynamics of Sorghum Food System in Ethiopia: Its Implications to Resolve Food Deficit - Teshome Sirany; Esubalew Tadele; Haimanot Aregahegn; Dagnachew Wale (Advances in Agriculture)
Agriculture continues to be vital to Africa’s future in both spatial and temporal contexts. Nonetheless, the sector keeps on confronting production challenges as a result of frequent and extended droughts, and these necessitate the use of drought-resistant crops such as sorghum. This review initiates one of the most common food grains grown in the poorest countries and the most food-insecure regions of the nation. We used deductive logical reasoning to develop a comprehensive scientific understanding of the crop that can be used to inform future research and policies. Various exclusion and inclusion criteria were used to filter the most prominent findings. Sorghum has the highest utility for its climatic adaptability and has grown for multiple purposes: From staple to industrial outcomes, its economic, social value, and health outcomes, and for animal silage. It is a gluten-free crop, has high nutritive value, and is preferred by healthy consumers. It is among the top five cereal crops worldwide in both production and acreage. This has necessitated the development of coping measures, such as the cultivation of drought-tolerant crops suitable for the affected areas. Therefore, this crop is used to ensure productivity, food security, and availability of food when other crops fail and food deficit and famine are affected in the region. This will contribute to the ongoing discussion on how to better inform private and public sector policy and investments in Ethiopia to increase sorghum and other drought-tolerant crop production, transform agriculture, improve nutrition, and food systems, and end hunger, food insecurity, and poverty.